2006
DOI: 10.1523/jneurosci.0491-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Molecular Effects of Dopamine D1 Receptor Stimulation during Naloxone-Precipitated Morphine Withdrawal

Abstract: Morphine dependence is characterized by somatic and motivational signs of withdrawal that likely contribute to the maintenance of addictive behavior. The nucleus accumbens (NAc) receives extensive dopaminergic input and is an important substrate for mediating these aversive states. In the NAc, the function of the transcription factor cAMP response element binding protein (CREB) and AMPA glutamate receptor subunit, type 1 (GluR1) can be regulated by dopamine (DA) D 1 receptor-mediated phosphorylation (P-CREB, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 60 publications
3
66
1
Order By: Relevance
“…Previous work from our laboratory and others (Harris and Aston-Jones, 1994;Chartoff et al, 2006;Chartoff et al, 2009;Radke et al, 2011) has demonstrated that dopamine receptor agonists attenuate withdrawal behaviors. The current experiments used two subtype-specific dopamine receptor agonists, SKF82958 and quinpirole, to examine the individual contributions of D1-and D2-like dopamine receptors, respectively, to this effect.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Previous work from our laboratory and others (Harris and Aston-Jones, 1994;Chartoff et al, 2006;Chartoff et al, 2009;Radke et al, 2011) has demonstrated that dopamine receptor agonists attenuate withdrawal behaviors. The current experiments used two subtype-specific dopamine receptor agonists, SKF82958 and quinpirole, to examine the individual contributions of D1-and D2-like dopamine receptors, respectively, to this effect.…”
Section: Introductionmentioning
confidence: 83%
“…Decreased dopaminergic activity has been shown to contribute to the production of negative emotional states (Stinus et al, 1990;Liu et al, 2008;Nestler and Carlezon, 2006) and manipulation of dopaminergic signaling attenuates conditioned place aversion (Bechara et al, 1995;Laviolette et al, 2002;Chartoff et al, 2006;but see Caillé et al, 2003) and other signs of opiate withdrawal (Harris and Aston-Jones, 1994;Rodríguez-Arias et al, 1999). Importantly, the initial increase in NAc dopamine release following acute exposure to 10 mg/kg of morphine would have largely dissipated at the time at which spontaneous withdrawal-potentiated startle is observed (Di Chiara and Imperato, 1988;Rothwell et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While acute morphine administration results in an increase in accumbal extracellular DA, microdialysis studies have shown that in response to chronic morphine, DA outflow is normal until withdrawal where there is a reduction (8)(9)(10). Systemic administration of the DA agonist SKF 82958 reduces somatic signs of morphine withdrawal while increasing phosphorylation of GluR1 in the Acb of morphine dependent rats treated with naloxone (18). Furthermore, in response to morphine withdrawal, there is a reduction in spine density that is specific to the dendrites of medium spiny neurons located in the AcbSh.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, direct administration of opioid antagonists in the amygdala of morphine-dependent animals is associated with moderate somatic withdrawal (13). Furthermore, systemic DA agonist administration attenuates both conditioned place aversions and somatic withdrawal symptoms in morphinedependent animals treated with naloxone, while increasing phosphorylation of GluR1 in the Acb (18), indirectly implicating the Acb in both withdrawal components. Altogether, these findings suggest a role for limbic structures in both somatic and motivational withdrawal.…”
Section: Introductionmentioning
confidence: 95%